2017
DOI: 10.1126/sciadv.aao1390
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality takes it to the streets: Mobilizing across diverse interests for the Women’s March

Abstract: Participants at the Women’s March were motivated by issues that cross identity and issue-based themes in systematic ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 41 publications
(57 reference statements)
10
73
1
Order By: Relevance
“…In addition, and as expected by our final hypothesis, we find that the issue of Reproductive Rights motivated people to turn out again and again, even when the respondents from the Women's March in 2018 are removed from the analysis. This finding in some ways replicates what other studies of protests in the Resistance have found: women and women's issues have been a major focus of the current cycle of contention ever since the 2017 Women's March (Fisher et al 2017;Meyer and Tarrow 2018;Putnam and Skocpol 2018). At the same time, the issue of Politics was negatively associated with persistence (second model) but positively associated with previous participation (first model).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, and as expected by our final hypothesis, we find that the issue of Reproductive Rights motivated people to turn out again and again, even when the respondents from the Women's March in 2018 are removed from the analysis. This finding in some ways replicates what other studies of protests in the Resistance have found: women and women's issues have been a major focus of the current cycle of contention ever since the 2017 Women's March (Fisher et al 2017;Meyer and Tarrow 2018;Putnam and Skocpol 2018). At the same time, the issue of Politics was negatively associated with persistence (second model) but positively associated with previous participation (first model).…”
Section: Discussionsupporting
confidence: 85%
“…In addition to these relevant studies that have looked specifically at differential recruitment, persistence, and differential participation, this article also builds on the small but growing literature on the Resistance itself. Although research has yet to assess what explains repeat participation in the protests during this specific cycle of contention, studies have looked at what were the main motivations for participants at the large-scale protest events within the Resistance (Fisher, Dow, and Ray 2017;Fisher et al 2018). In these studies, when controlling for a number of variables including protest experience, the authors find that there were overlapping patterns of motivations for participants that span the progressive agenda.…”
Section: Studying Differential Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a long‐term research project on protest, I worked with a 12‐person research team to study the March for Science in Washington, DC, on April 21, 2017. Employing a methodology that has been developed over a series of empirical investigations of activism and protest in the United States (Fisher, Dow, and Ray ; Fisher, Stanley, Berman, and Neff ; see also Heaney and Rojas ), we surveyed the crowd at the event using a field approximation of random selection. While participants listened to speeches and tried to avoid the rain, researchers snaked through the crowd surveying every fifth person in the area designated for the staging of the March on the grounds of the Washington Monument.…”
Section: Learning From the March For Sciencementioning
confidence: 99%
“…Undoubtedly, part of the reason for this mass mobilization was the activists' use of digital and social media (McKane and McCammon 2018). Like many contemporary social movements, the Women's March mobilized through the use of information and communication technologies (ICTs); in fact, it began originally as a Facebook event (Fisher et al 2017). These technologies were invaluable in spreading information about the Women's March, including how to travel to Washington, DC, and where to find a local march if such travel was impossible.…”
Section: Introductionmentioning
confidence: 99%